A method for preparing hydrophilic carbon fiber

By using hydrophilic polymer-modified carbon fiber method during the preparation of carbon fiber paper, domestic carbon fiber paper has been solved, and the problems of low mechanical strength and poor electrical performance in fuel cell applications have been achieved, achieving better dispersion and performance improvement.

CN118186770BActive Publication Date: 2025-03-11HARBIN INST OF TECH AT WEIHAI +1

Patent Information

Application Number
CN202410414631.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-08
Publication Date
2025-03-11
Estimated Expiration
2044-04-08

AI Technical Summary

Technical Problem

Domestic carbon fiber paper has problems such as low mechanical strength, poor electrical performance and poor pore size distribution in fuel cell applications, resulting in uneven dispersion during the beating and papermaking process, affecting performance.

Method used

Using a hydrophilic carbon fiber preparation method, the hydrophilic polymer is dissolved in a buffer solution and completely dissolved under ultrasonic conditions, and then the solution is immersed in the carbon fiber and dried to impart hydrophilicity to the carbon fiber surface.

Benefits of technology

The dispersion of carbon fiber under aqueous conditions is improved, the problem of uneven dispersion is solved, the conductivity and mechanical properties of carbon fiber paper are enhanced, and it is suitable for gas diffusion layers of fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118186770B_ABST
    Figure CN118186770B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing hydrophilic carbon fiber, belonging to the technical field of carbon fiber materials. Glycidyl methacrylate and methyl methacrylate ethyl sulfobetaine are copolymerized by free radical polymerization to prepare a controllable amphiphilic copolymer; the amphiphilic copolymer is blended with dopamine, and a ternary system polymer is prepared by reacting an epoxy group with an amino group. Under alkaline solution conditions, the adhesion of dopamine after self-polymerization is utilized to introduce hydrophilic zwitterionic groups to the fiber surface to achieve sizing function, and to give the carbon fiber surface hydrophilic properties, so that it has better fiber opening in water, and achieves the effect of complete dispersion under aqueous conditions. The preparation method can ensure the strength of carbon paper while improving the dispersibility of carbon fiber, has important application prospects, and has a simple process and can meet the needs of large-scale industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon fiber materials, and in particular to a method for preparing hydrophilic carbon fiber. Background Art

[0002] Proton exchange membrane fuel cell (PEMFC) is an energy conversion device that converts the chemical energy of fuel into clean electricity that is easy for humans to use through electrochemical reactions. The gas diffusion layer (GDL) is one of the key components in the PEMFC membrane electrode. It is embedded between the catalyst layer and the gas flow channel of the membrane electrode, supports the catalyst layer, provides an important mass transfer channel for the reaction gas and the generated water, and also plays the role of transmitting electrical energy. The GDL needs to allow the gas to reach the catalyst layer and discharge the liquid phase water of the reaction product. It needs to enhance the transfer of reactants to the catalytic active sites under the premise of preventing flooding. The ideal GDL should have the following characteristics: optimal bending stiffness, porosity, surface contact angle, air permeability, water vapor diffusion, hydrophilicity and hydrophobicity, corrosion resistance, crack-free surface morphology, high mechanical integrity and enhanced oxidation stability. The preparation of GDL usually uses high-performance carbon fiber paper as the base material. The performance and specifications of carbon fiber paper will directly affect the performance of GDL. Carbon fiber paper is prepared by carbon fiber dispersion, papermaking, curing, and carbonization processes. The dispersion performance of carbon fiber determines the conductive properties of carbon fiber paper and is the key to its preparation.

[0003] At present, the production technology of carbon fiber paper for fuel cells is basically mastered by foreign countries. Due to the early development of the carbon fiber industry in developed countries abroad and the low cost, the production process technology of carbon fiber paper has gradually matured. At present, there are only a few companies that can supply in batches, such as Ballard Material Products in Canada, SGL Technology in Germany and Toray in Japan. Carbon fiber paper production technology has become one of the main obstacles to the development of fuel cells in my country. my country urgently needs to develop domestic high-performance carbon fiber paper with independent intellectual property rights to meet the needs of fuel cells. At present, domestic carbon fiber paper has made a certain degree of progress. However, the problems of low mechanical strength, poor electrical performance and poor pore size distribution of carbon fiber paper are still urgently needed to be solved. At present, domestic fuel cell research still uses imported carbon fiber paper. There are many reasons for this phenomenon. In addition to the gap between the performance and price of domestic carbon fiber and market expectations, the main reason is that the surface of carbon fiber is very smooth and cannot be pulped to make its surface silk broom. The fibers cannot be combined to form paper by forming hydrogen bonds like plant fibers, which further leads to poor interface bonding between paper and resin matrix, which seriously affects the strength and related properties of carbon fiber paper. Therefore, it is of great practical significance to develop hydrophilic carbon fiber to prepare carbon fiber paper with independent intellectual property rights. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing hydrophilic carbon fiber, improve the dispersion of carbon fiber under aqueous conditions, and solve the problem of uneven dispersion during pulping and papermaking of carbon fiber carbon paper.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing hydrophilic carbon fiber comprises the following steps:

[0007] S1, dissolving a hydrophilic polymer in a buffer solution, and sonicating until the polymer is completely dissolved to obtain a solution A;

[0008] S2. Add solution A into the slurry tank, immerse the carbon fiber in the slurry tank for 8-12 hours, take out and dry to obtain surface hydrophilic modified carbon fiber.

[0009] Preferably, the amount of the hydrophilic polymer added in S1 is 2.45-6.95 g.

[0010] Preferably, the amount of buffer solution added in S1 is 800-2000 mL.

[0011] Preferably, the buffer solution in S1 has a pH of 8.5-10.0 tirs.

[0012] Preferably, the ultrasonic conditions in S1 are frequency 20-60 kHz, time 0.5-2 h, and temperature 25-40°C.

[0013] Preferably, the drying temperature in S2 is 60-90° C. and the drying time is 24-48 hours.

[0014] The general structural formula of the hydrophilic polymer in S1 is shown in formula (1):

[0015]

[0016] Among them, 5≤x≤15, 5≤y≤15.

[0017] Furthermore, the method for synthesizing the hydrophilic polymer comprises the following steps:

[0018] (1) dissolving glycidyl methacrylate and methyl methacryloylethyl sulfobetaine in chloroform, adding azobisisobutyronitrile (AIBN) for heating reaction, and obtaining a mixed system;

[0019] (2) rotary evaporating the solvent of the mixed system obtained in step (1) to obtain a solid polymer;

[0020] (3) dissolving the solid polymer obtained in step (2) in 50-100 mL of ethanol and aqueous solution, adding dopamine, and heating to react to obtain a mixed system;

[0021] (4) Rotate the mixed system obtained in step (3) to evaporate the solvent to obtain a hydrophilic polymer.

[0022] Preferably, in step (1), the amount of glycidyl methacrylate added is 0.5-2.5 g, the amount of methacryloylethyl sulfobetaine added is 0.98-4.92 g, and the amount of chloroform added is 80-150 mL.

[0023] Preferably, the amount of azobisisobutyronitrile added in step (1) is 0.02-0.05 g.

[0024] Preferably, the heating reaction temperature in step (1) is 65-90°C and the time is 12-24h.

[0025] Preferably, the rotary evaporation temperature in step (2) is 90° C. and the time is 3-6 hours.

[0026] Preferably, in step (3), the amount of solid polymer added is 0.65-1.28 g, and the amount of dopamine added is 0.53-1.05 g.

[0027] Preferably, in step (3), the ratio of ethanol to deionized water is 2:1.

[0028] Preferably, the heating reaction temperature in step (3) is 65-90°C and the time is 12-24h.

[0029] Preferably, the rotary evaporation temperature in step (4) is 100° C. and the time is 3-6 h.

[0030] The synthetic route of the hydrophilic polymer is as follows:

[0031]

[0032] Among them, 5≤x≤15, 5≤y≤15.

[0033] The present invention also provides a method for verifying the hydrophilicity of carbon fiber, and the specific method is as follows:

[0034] Dissolve polyacrylamide in water, heat and stir until completely dissolved, chop the obtained surface hydrophilic modified carbon fiber into short pieces, add it to the polyacrylamide solution, first use a glass rod to stir and pre-disperse for 2 minutes, and then ultrasonically disperse it at an ultrasonic power of 45kHz for 5 minutes. The carbon fiber concentration is controlled at a mass fraction of 0.001%-0.005% to obtain a carbon fiber aqueous solution dispersed under aqueous conditions.

[0035] Preferably, the amount of polyacrylamide added in S2 is 0.25-2.0 g.

[0036] Preferably, the amount of water added to S2 is 100-300g.

[0037] Preferably, the heating and stirring conditions in S2 are a temperature of 60-80° C. and a heating time of 4-8 h.

[0038] The technical scheme principle and effect of the present invention: the hydrophobic structure is used to react with dopamine later, and the hydrophilic structure is introduced into the fiber surface by utilizing the adhesion of dopamine, thereby realizing the regulation of the hydrophilic performance of the fiber surface. Glycidyl methacrylate and methyl methacrylate ethyl sulfobetaine are copolymerized by free radical polymerization to prepare a structure-controllable amphiphilic copolymer, whose hydrophilic structure ratio is 5≤y≤15 and hydrophobic structure is 5≤x≤15. The amphiphilic copolymer is blended with dopamine, and its hydrophobic structure reacts with dopamine. The ternary system polymer is prepared by reacting epoxy groups with amino groups. Under alkaline solution conditions, the adhesion of dopamine after self-polymerization is utilized to introduce hydrophilic zwitterionic groups to the fiber surface to realize the sizing function and give the carbon fiber surface hydrophilic properties, so that it has better fiber opening properties in water, and achieves the effect of complete dispersion under aqueous conditions.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] 1. Through sizing treatment of carbon fiber with a sizing agent of a specific structure, the adhesion of dopamine after polymerization is utilized to introduce hydrophilic zwitterionic groups into the fiber surface, which gives the carbon fiber surface hydrophilic properties and enables it to have better fiber opening in water, achieving the effect of complete dispersion at low concentrations.

[0041] 2. The operation process of the present invention is relatively simple, the operation is environmentally friendly, no toxic solvents are used, and it can be prepared on a large scale, which has important application prospects.

[0042] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a digital photo of the aqueous dispersion of carbon fibers prepared in Example 1 of the present invention;

[0044] Figure 2 This is a digital photo of the aqueous dispersion of carbon fibers prepared in Example 2 of the present invention;

[0045] Figure 3 This is a digital photo of the aqueous dispersion of carbon fibers prepared in Example 3 of the present invention;

[0046] Figure 4This is a digital photo of an untreated carbon fiber aqueous dispersion;

[0047] Figure 5 This is a scanning electron microscope image of the surface morphology of the carbon fiber prepared in Example 1 of the present invention;

[0048] Figure 6 This is a scanning electron microscope image of the surface morphology of the carbon fiber prepared in Example 2 of the present invention;

[0049] Figure 7 This is a scanning electron microscope image of the surface morphology of the carbon fiber prepared in Example 3 of the present invention;

[0050] Figure 8 This is a scanning electron microscope image of the surface morphology of untreated carbon fiber;

[0051] Fig. 9 This is an atomic force microscope image of the surface morphology of the carbon fiber prepared in Example 1 of the present invention;

[0052] Fig.10 This is an atomic force microscope image of the surface morphology of the carbon fiber prepared in Example 2 of the present invention;

[0053] Fig.11 This is an atomic force microscope image of the surface morphology of the carbon fiber prepared in Example 3 of the present invention;

[0054] Fig.12 Atomic force microscopy image of the untreated carbon fiber surface morphology. DETAILED DESCRIPTION

[0055] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0056] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0057] Embodiment 1 This embodiment provides a method for preparing a hydrophilic carbon fiber, comprising the following steps:

[0058] Step 1: Dissolve 0.5 g of glycidyl methacrylate and 0.98 g of methacryloylethyl sulfobetaine in 120 mL of chloroform, add 0.025 g of azobisisobutyronitrile AIBN, react at 75° C. for 16 h to polymerize to obtain a mixed system, place the mixed system in a 90° C. water bath and rotary evaporate the solvent for 3.5 h to obtain a solid substance;

[0059] Step 2: Dissolve 0.65 g of the polymer obtained above in 55 mL of ethanol and water solution (V / V 2:1), add 0.53 g of dopamine, heat at 65° C. for 14 h, and evaporate the solvent in a 100° C. water bath for 4 h to obtain a solid substance.

[0060] Step 3: Dissolve 2.45 g of hydrophilic polymer in 830 mL of pH 8.5 tirs buffer solution, and ultrasonicate at 35 kHz for 0.5 h at 28 °C until the polymer is completely dissolved to obtain solution A. Add solution A to the slurry tank, immerse the carbon fiber in the slurry tank for 8 h, then take out and dry at 65 °C for 24 h to obtain surface hydrophilically modified carbon fiber.

[0061] Embodiment 2 This embodiment provides a method for preparing a hydrophilic carbon fiber, comprising the following steps:

[0062] Step 1: Dissolve 1.25 g of glycidyl methacrylate and 2.24 g of methacryloylethyl sulfobetaine in 135 mL of chloroform, add 0.035 g of azobisisobutyronitrile AIBN, react at 85° C. for 18 h to obtain a mixed system, place the mixed system in a 90° C. water bath and rotary evaporate the solvent for 4 h to obtain a solid substance;

[0063] Step 2: Dissolve 1.25 g of the polymer obtained above in 85 mL of ethanol and water solution (V / V 2:1), add 0.86 g of dopamine, heat at 75° C. for 18 h, and evaporate the solvent in a 100° C. water bath for 4.5 h to obtain a solid substance.

[0064] Step 3: Dissolve 3.55 g of hydrophilic polymer in 1550 mL of pH 8.5 tirs buffer solution, and ultrasonicate at 40 kHz for 0.8 h at 32 °C until the polymer is completely dissolved to obtain solution A. Add solution A to the slurry tank, immerse the carbon fiber in the slurry tank for 10 h, then take out and dry at 75 °C for 24 h to obtain surface hydrophilically modified carbon fiber.

[0065] Embodiment 3 This embodiment provides a method for preparing a hydrophilic carbon fiber, comprising the following steps:

[0066] Step 1: 2.25 g of glycidyl methacrylate and 3.86 g of methacryloylethyl sulfobetaine were dissolved in 150 mL of chloroform, and 0.045 g of azobisisobutyronitrile (AIBN) was added to react at 90° C. for 24 h to polymerize to obtain a mixed system, and the mixed system was placed in a 90° C. water bath and the solvent was rotary evaporated for 4.5 h to obtain a solid substance;

[0067] Step 2: Dissolve 1.28 g of the polymer obtained above in 100 mL of ethanol and water solution (V / V 2:1), add 1.00 g of dopamine, heat to 80° C. for 24 h, and evaporate the solvent in a 100° C. water bath for 5.5 h to obtain a solid substance.

[0068] Step 3: Dissolve 5.25 g of hydrophilic polymer in 1880 mL of pH 8.5 tirs buffer solution, and ultrasonicate at 55 kHz for 1.6 h at 35 °C until the polymer is completely dissolved to obtain solution A. Add solution A to the slurry tank, immerse the carbon fiber in the slurry tank for 12 h, then take out and dry at 85 °C for 36 h to obtain surface hydrophilically modified carbon fiber.

[0069] The effect of the present invention is verified by the following experimental tests:

[0070] 1. Hydrophilicity test: Four tested materials (carbon fiber prepared in Example 1, carbon fiber prepared in Example 2, carbon fiber prepared in Example 3, and untreated carbon fiber) were subjected to hydrophilicity test.

[0071] Example 1 Preparation of carbon fiber aqueous solution: Dissolve 0.28g polyacrylamide in 120g water, heat and stir at 65°C for 4.5h to fully dissolve, cut the surface hydrophilic modified carbon fiber prepared in Example 1 into 3.5mm short pieces, add them to the polyacrylamide solution, first use a glass rod to stir and pre-disperse for 2min, ultrasonically disperse at an ultrasonic power of 45kHz for 5min, control the carbon fiber concentration at a mass fraction of 0.0015%, and obtain a carbon fiber aqueous solution dispersed under aqueous conditions.

[0072] Example 2 Preparation of carbon fiber aqueous solution: 1.24 g of polyacrylamide was dissolved in 180 g of water, heated and stirred at 68°C for 6.2 h to fully dissolve, the surface hydrophilic modified carbon fiber prepared in Example 2 was chopped into 4.0 mm, added to the polyacrylamide solution, first pre-dispersed with a glass rod for 2 min, and ultrasonically dispersed at an ultrasonic power of 45 kHz for 5 min. The carbon fiber concentration was controlled at a mass fraction of 0.0025% to obtain a carbon fiber aqueous solution dispersed under aqueous conditions.

[0073] Example 3 Preparation of carbon fiber aqueous solution: 1.68 g of polyacrylamide was dissolved in 240 g of water, heated and stirred at 75°C for 7 h to fully dissolve, the surface hydrophilic modified carbon fiber prepared in Example 3 was chopped into 4.5 mm, added to the polyacrylamide solution, first pre-dispersed with a glass rod for 2 min, and ultrasonically dispersed at an ultrasonic power of 45 kHz for 5 min. The carbon fiber concentration was controlled at a mass fraction of 0.0040% to obtain a carbon fiber aqueous solution dispersed under aqueous conditions.

[0074] Preparation of untreated carbon fiber aqueous solution: Dissolve 0.28g polyacrylamide in 120g water, heat and stir at 65°C for 4.5h to fully dissolve, chop the untreated carbon fiber into 3.5mm, add it to the polyacrylamide solution, first use a glass rod to stir and pre-disperse for 2min, ultrasonically disperse at an ultrasonic power of 45kHz for 5min, control the carbon fiber concentration at a mass fraction of 0.0015%, and obtain an untreated carbon fiber aqueous solution.

[0075] The above-obtained carbon fiber aqueous solutions of Examples 1-3 and untreated carbon fiber were photographed with a digital camera after 6 hours to observe the dispersion effect of the fiber in the aqueous solution.

[0076] Digital photos of aqueous dispersions of four tested materials (carbon fiber prepared in Example 1, carbon fiber prepared in Example 2, carbon fiber prepared in Example 3, and untreated carbon fiber) are shown in Figure 1-4 As can be seen from the figure, after Example 1 ( Figure 1 )、Example 2( Figure 2 ) and Example 3 ( Figure 3 ) prepared hydrophilic carbon fiber was dispersed in polyacrylamide solution. After 6 hours, the short chopped carbon fiber did not agglomerate and the carbon fiber was well dispersed, indicating that the surface of the carbon fiber prepared by this method was hydrophilic and suitable for further making carbon fiber paper. It can meet the conductivity of carbon fiber paper, while the untreated carbon fiber ( Figure 4 ), a large number of short-cut carbon fibers agglomerated rapidly in polyacrylamide solution, and the agglomeration phenomenon was obvious, indicating that the carbon fibers did not have hydrophilic properties and were not suitable for use as fuel cell carbon paper.

[0077] 2. Surface morphology analysis:

[0078] The surface morphology scanning electron microscope images of the carbon fiber prepared in Example 1, the carbon fiber prepared in Example 2, the carbon fiber prepared in Example 3, and the untreated carbon fiber are shown in FIG. Figure 5-8 As shown in the figure, it can be seen that after Example 1 ( Figure 1 )、Example 2( Figure 2 ) and Example 3 ( Figure 3 ) prepared hydrophilic carbon fiber, the fiber surface is relatively smooth, the groove is relatively shallow, indicating that the hydrophilic compound prepared in this embodiment has been evenly coated on the fiber surface, giving the fiber surface a hydrophilic effect, thereby achieving the effect of uniform dispersion of the carbon fiber under aqueous conditions; while the untreated carbon fiber ( Figure 4 ), the fiber surface is uneven, and the deep grooves on the carbon fiber surface can be clearly seen, indicating that the carbon fiber does not have hydrophilic properties and the dispersion performance of the carbon fiber has not been improved.

[0079] 3. Surface morphology atomic force microscope analysis:

[0080] Atomic force microscope images of the carbon fiber prepared in Example 1, the carbon fiber prepared in Example 2, the carbon fiber prepared in Example 3, and the untreated carbon fiber are shown in FIG. Figure 9-12 As shown in Example 1 ( Figure 1 )、Example 2( Figure 2 ) and Example 3 ( Figure 3 ) prepared hydrophilic carbon fiber, the fiber surface is relatively smooth, no obvious bubbles and grooves are found, indicating that the hydrophilic compound prepared in this example has been evenly coated on the fiber surface, filling the grooves on the fiber surface, giving the fiber surface a hydrophilic effect, and achieving the purpose of uniform dispersion of carbon fiber under aqueous conditions; while the untreated carbon fiber ( Figure 4 ), the bubbling phenomenon and grooves on the fiber surface are clearly visible, which is a defect in the fiber production process. This structure causes the fiber to easily agglomerate under aqueous conditions. Therefore, the carbon fibers prepared in Examples 1-3 have obvious improvements in surface structure compared to the untreated carbon fibers.

[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a hydrophilic carbon fiber, characterized in that: The steps include: S1, dissolving a hydrophilic polymer in a buffer solution, and sonicating until the polymer is completely dissolved to obtain a solution A; S2, adding solution A into the slurry tank, immersing the carbon fiber in the slurry tank for 8-12 hours, taking out and drying, to obtain surface hydrophilic modified carbon fiber; The pH of the buffer solution in S1 is 8.5-10.0; Frequency 20-60kHz, time 0.5-2h, temperature 25-40℃; The drying temperature in S2 is 60-90°C and the drying time is 24-48h; The hydrophilic polymer has a general structural formula as shown in formula (1): Among them, 5≤x≤15, 5≤y≤15; The hydrophilic polymer, its synthesis method comprises the following steps: (1) dissolving glycidyl methacrylate and methyl methacryloylethyl sulfobetaine in chloroform, adding azobisisobutyronitrile (AIBN), and heating to react to obtain a mixed system; (2) rotary evaporating the solvent of the mixed system obtained in step (1) to obtain a solid polymer; (3) dissolving the solid polymer obtained in step (2) in 50-100 mL of ethanol and aqueous solution, adding dopamine, and heating to react to obtain a mixed system; (4) rotary evaporating the solvent of the mixed system obtained in step (3) at 100° C. for 3-6 hours to obtain a hydrophilic polymer; In the step (3), the ratio of ethanol to deionized water is 2:

1.

2. The method for preparing a hydrophilic carbon fiber according to claim 1, characterized in that: In step (1), the heating reaction temperature is 65-90° C. and the time is 12-24 h.

3. The method for preparing a hydrophilic carbon fiber according to claim 1, characterized in that: The rotary evaporation temperature in step (2) is 90° C. and the time is 3-6 h.

4. The method for preparing a hydrophilic carbon fiber according to claim 1, characterized in that: In step (3), the heating reaction temperature is 65-90° C. and the time is 12-24 h.

Citation Information

Patent Citations

  • Preparation method of grafted hydrophilic polymer bionic ultrafiltration membrane

    CN110743371A

  • Water-based carbon fiber sizing agent as well as preparation method and application thereof

    CN117646327A

Cited By

  • Preparation method of viscose-based carbon fiber aqueous slurry based on composite dispersion synergistic effect

    CN120401223A